Age at menopause and risk of heart failure and atrial fibrillation: a nationwide cohort study . (4th August 2022) - Shin, Jean; Han, Kyungdo; Jung, Jin-Hyung; Park, Hyo Jin; Kim, Wonsock; Huh, Youn; Kim, Yang-Hyun; Kim, Do-Hoon; Kim, Seon Mee; Choi, Youn Seon; Cho, Kyung Hwan; Nam, Ga Eun
Abstract: Aims: This study aimed to examine the association of premature menopause and age at menopause with the risk of heart failure (HF) and atrial fibrillation (AF). Methods and results: A total of 1 401 175 postmenopausal women, who had undergone health examination provided by the Korean National Health Insurance Service, were included, and their reproductive histories were collected. Multivariable Cox proportional hazard models were performed to determine the hazard ratios (HRs) and 95% confidence intervals (CIs) of incident HF and AF, according to the history of premature menopause and age at menopause. At a mean follow-up of 9.1 years, there were 42 699 (3.0%) and 44 834 (3.2%) new cases of HF and AF, respectively. Women with history of premature menopause had an increased risk of HF (HR: 1.33, 95% CI: 1.26–1.40) and AF (HR: 1.09, 95% CI: 1.02–1.16), compared to women without the history. Compared with women aged ≥50 years at menopause, those aged 45−49, 40−44, and <40 years at menopause showed a significantly increased trend in HRs for the incident risk of both HF and AF ( P for trend <0.001). The robustness of the results of a series of sensitivity analyses further strengthens the main findings. Conclusion: Our findings suggest that postmenopausal women with a history of premature menopause or early menopausal age may have an increased risk of HF and AF. These reproductive factors need to be considered for preventing the future risk of HF and AF. Abstract : This study showed that a history of premature menopause and early menopausal age was associated with an increased risk of both heart failure and atrial fibrillation in postmenopausal women. Structured Graphical Abstract: Structured Graphical Abstract Evidence on the association between age at menopause and the risk of heart failure and atrial fibrillation is limited. Analysis results on 1 401 175 postmenopausal women based on the Korean National Health Insurance database showed that women with a history of premature or early menopausal age may have an increased risk of heart failure and atrial fibrillation.